The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.ygyno.2016.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Tumor mutational analysis of GOG248, a phase II study of temsirolimus or temsirolimus and alternating megestrol acetate and tamoxifen for advanced endometrial cancer (EC): An NRG Oncology/Gynecologic Oncology Group study

Abstract: Objective Rapamycin analogs have reproducible but modest efficacy in endometrial cancer (EC). Identification of molecular biomarkers that predict benefit could guide clinical development. Methods Fixed primary tissue and whole blood were collected prospectively from patients enrolled on GOG 248. DNA was isolated from macro-dissected tumors and blood; next–generation sequence analysis was performed on a panel of cancer related genes. Associations between clinical outcomes [response rate (RR) 20%; progression-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 34 publications
(35 reference statements)
1
14
0
Order By: Relevance
“…Mutations in TSC2, although uncommon, have previously been reported in endometrial cancer as well as other tumor types to be associated with clinical response to mTOR inhibition [20, 21]. TSC2 somatic mutations were identified here in 14 (5.8%) patients.…”
Section: Resultsmentioning
confidence: 53%
“…Mutations in TSC2, although uncommon, have previously been reported in endometrial cancer as well as other tumor types to be associated with clinical response to mTOR inhibition [20, 21]. TSC2 somatic mutations were identified here in 14 (5.8%) patients.…”
Section: Resultsmentioning
confidence: 53%
“…However, no advantage was found from the addition of the mTOR inhibitor temsirolimus to standard carboplatin and paclitaxel chemotherapy, and multiple trials of single‐agent rapamycin‐analog mTOR inhibitors in advanced or recurrent disease have shown only modest activity (<25% response rates even in the setting of chemotherapy‐naive disease), and no association between activity and PTEN or PIK3CA alterations has been observed. One report noted significantly increased PFS and response rates in 3 patients whose tumors had AKT1 mutations …”
Section: Future Directionsmentioning
confidence: 99%
“…Several studies have shown no association between tumor PTEN alterations or PI3KCA mutations and clinical benefit from mTOR inhibitors. One report did describe a significant increase in RR and PFS for patients with an activating AKT mutation treated with temsirolimus, suggesting this population, although small, may derive particular benefit from treatment with mTOR inhibitors [94].…”
Section: Molecularly Targeted Therapymentioning
confidence: 99%